REPRESENTASI MOTIF PENDUKUNG LUKISAN KAMASAN KERTHA GOSA PADA BATIK DALAM BUSANA MODIFIKASI BALI DENGAN TEKNIK ZERO WASTE - Ni Made Gadis Putri Maharani (Batarirupa: Jurnal Pendidikan Seni, 2023)
Kertha Gosa is a courthouse inherited from the Semarapura Palace. There are three relics of the Semarapura Palace, namely, Bale Kertha Gosa, Bale Kambang, the Semarapura Museum building with a European architectural style which was previously a former Dutch school. Interestingly, in every Kertha Gosa building, there are various kinds of Kamasan paintings which are often associated with Balinese historical stories. This painting has a very prominent characteristic and each painting has a deep meaning or philosophy. The Kamasan painting found in the Kertha Gosa building is a source of ideas for batik motifs as a material for making casual clothes combined with Balinese modifications. Creation methods include methods of data collection, data analysis, work design, and work embodiment. The application of the creation method is used to strengthen the concept from observation to the realization of the work. The making of this work also uses a technique, namely Zero Waste. In the world of fashion, the Zero Waste technique is a movement to reduce or make clothing without producing textile waste in it. The entire work has a different title from the simple depiction of the Kamasan painting found in the Kertha Gosa building which has unique characteristics and meaning. This work was made with the aim that the Indonesian people know, do not easily forget and love history - history or culture that they have.